A felt and its preparation method and application
Patent Information
- Application Number
- CN202411486592.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-10-23
AI Technical Summary
然而,由于固毡是通过回收再利用废旧软毡制成的,其原始的柔软性和热传导性能可能有所降低,导致其保温性能有所下降
[0018](1)本发明提供的固毡,在固毡的内部设置了若干个环形空腔,内部利用环形空腔中的空气进行热量的传递,而空气传递热量的速度相对于固毡基体传递热量的速度小,从而提高了固毡的保温性能;在环形空腔的表面设置固化涂层,有利于提高固毡的导电性和耐用性。
Smart Images

Figure CN119348241B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor crystal manufacturing, and more specifically, to a solid felt, its preparation method, and its application. Background Technology
[0002] The manufacturing process of cured felt used for pulling single crystals includes steps such as felt cutting, adhesive preparation, adhesive application, molding, high-temperature drying, machining, coating, high-temperature calcination, and testing. In existing cured felt layering and curing processes, the insulation effect of the cured felt is inferior to that of soft felt.
[0003] Compared to soft felt, solid felt offers better stability and durability, while soft felt excels in thermal conductivity and insulation. Both solid and soft felt are types of graphite felt, but they differ in manufacturing processes, performance, and applications. Solid felt is made from recycled waste soft felt. Its preparation method involves crushing the waste soft felt into small pieces, adding graphite adhesive and anhydrous ethanol solvent, stirring, filling the mixture into a mold, pressing it into shape, and finally demolding to obtain solid felt.
[0004] This preparation method improves the stability of the solid felt, enabling its wide application in various situations requiring stable support. However, since the solid felt is made from recycled waste soft felt, its original softness and thermal conductivity may be reduced, resulting in a decrease in its thermal insulation performance.
[0005] In view of this, the present invention is hereby proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a solid felt, its preparation method and application, wherein the solid felt has advantages such as good heat insulation, electrical conductivity, stability and durability.
[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:
[0008] One aspect of the present invention relates to a solid felt, comprising: a substrate and a plurality of annular cavities disposed within the substrate;
[0009] The surface of the annular cavity is provided with a cured coating.
[0010] The aforementioned solid felt has good thermal insulation properties, excellent electrical conductivity, stability, and durability, which can improve the service life of photovoltaic materials and reduce production costs.
[0011] Another aspect of the present invention relates to a method for preparing the aforementioned solid felt, comprising the following steps:
[0012] (a) Liquid coating is filled into a container to obtain a filler; annular soft felt is stacked to obtain a soft felt precursor;
[0013] (b) A space for accommodating the filler is processed in the soft felt precursor, and the filler is filled into the soft felt precursor to obtain a cured felt preform;
[0014] (c) The cured felt blank is subjected to heating and rotation treatment and first cooling.
[0015] The method for preparing the solid felt is simple and does not require complex processes and equipment. The solid felt prepared has good thermal insulation properties, while also taking into account the advantages of stability, conductivity and durability.
[0016] Another aspect of the present invention relates to a semiconductor crystal manufacturing apparatus, comprising the aforementioned solid felt or a solid felt prepared by the aforementioned solid felt preparation method.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0018] (1) The solid felt provided by the present invention has several annular cavities inside the solid felt. The air in the annular cavities is used to transfer heat. The heat transfer speed of the air is smaller than that of the solid felt matrix, thereby improving the heat insulation performance of the solid felt. A curing coating is provided on the surface of the annular cavities, which is beneficial to improving the conductivity and durability of the solid felt.
[0019] (2) The method for preparing solid felt provided by the present invention is simple and does not require complex processes and equipment. A filler is placed in the soft felt precursor, and several annular cavities are formed inside the solid felt by heating, rotating and cooling. The solid felt prepared by this method has good heat preservation performance, while also taking into account the advantages of stability, conductivity and durability. Attached Figure Description
[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 A cross-sectional view of the solid felt provided in an embodiment of the present invention;
[0022] Figure 2 This is an overall view of the solid felt provided in an embodiment of the present invention. Detailed Implementation
[0023] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0024] One aspect of the present invention relates to a felt, such as Figure 1 and Figure 2 As shown, it includes: a matrix and a plurality of annular cavities disposed inside the matrix;
[0025] The surface of the annular cavity is provided with a cured coating.
[0026] The solid felt has several annular cavities inside, and heat is transferred by the air in the annular cavities. Since the air transfers heat at a slower rate than the solid felt matrix, the heat insulation performance of the solid felt is improved. A curing coating is applied to the surface of the annular cavities, which helps to improve the conductivity and durability of the solid felt.
[0027] Furthermore, the diameter of the annular cavity is 20-30 mm, including but not limited to a point value of any one of 20 mm, 22 mm, 24 mm, 26 mm, 28 mm, or 30 mm, or a range between any two. The diameter of the annular cavity refers to the diameter of the cavity body.
[0028] Furthermore, taking the cross-sectional area per square meter of the solid felt as the unit area, the number of annular cavities set within the unit area is 350 to 790, including but not limited to any one of 350, 380, 400, 430, 450, 480, 500, 530, 550, 580, 600, 630, 650, 680, 700, 730, 750, or 790, or a range between any two.
[0029] To ensure the strength of the solid felt, the smaller the diameter of the annular cavity, the more annular cavities can be designed, and the better the thermal insulation. However, the manufacturing process becomes more complicated as the diameter of the annular cavity decreases, while the number of annular cavities decreases as the diameter increases.
[0030] Furthermore, the distance between two adjacent annular cavities is 30-60 mm, including but not limited to a single value of 30 mm, 40 mm, 50 mm, or 60 mm, or a range between any two. A certain distance must be maintained between the annular cavities; if the distance is too small, it will affect the structural strength of the felt.
[0031] Furthermore, the thickness of the cured coating is 2–4 mm, including but not limited to a single value of 2 mm, 2.5 mm, 3 mm, 3.5 mm, or 4 mm, or a range between any two. Limiting the thickness of the cured coating within a certain range ensures that the annular cavity has sufficient cavity space and improves the thermal insulation performance of the cured felt.
[0032] Further, based on parts by weight, the cured coating comprises the following components:
[0033] The ingredients include 5-6 parts binder, 4-5 parts graphite, 21-23 parts silicon carbide, 1-2 parts carbon fiber powder, 0.5-2 parts fumed silica powder, 9-11 parts triethanolamine borate, and 7-9 parts additives.
[0034] In some specific embodiments, in the cured coating, the adhesive, by weight parts, can be, for example, but not limited to, any one of 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, or 6 parts, or a range between any two; the graphite can be, for example, but not limited to, any one of 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, or 5 parts, or a range between any two; the silicon carbide can be, for example, but not limited to, any one of 21 parts, 21.2 parts, 21.4 parts, 21.6 parts, 21.8 parts, 22 parts, 22.2 parts, 22.4 parts, 22.6 parts, 22.8 parts, or 23 parts, or a range between any two; the carbon fiber can be, for example, but not limited to, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, or 2... The point value of any one of the parts or the range between any two; fumed silica, for example, can be, but is not limited to, any one of 0.5 parts, 0.7 parts, 0.9 parts, 1.1 parts, 1.3 parts, 1.5 parts, 1.7 parts or 2 parts, or the range between any two; triethanolamine borate, for example, can be, but is not limited to, any one of 9 parts, 9.2 parts, 9.4 parts, 9.6 parts, 9.8 parts, 10.0 parts, 10.2 parts, 10.4 parts, 10.6 parts, 10.8 parts or 11 parts, or the range between any two; additives, for example, can be, but is not limited to, any one of 7 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts, 8 parts, 8.2 parts, 8.4 parts, 8.6 parts, 8.8 parts or 9 parts, or the range between any two.
[0035] Furthermore, the adhesive includes, but is not limited to, furan resin.
[0036] Furthermore, the additive comprises yttrium silicate and aluminum tantalate in a mass ratio of 1:1 to 3 (e.g., but not limited to 1:1, 1:2, or 1:3). The additive acts as a catalyst during the curing process, accelerating the curing reaction of the furan resin and increasing the hardness of the felt coating.
[0037] Another aspect of the present invention relates to a method for preparing the aforementioned solid felt, comprising the following steps:
[0038] (a) Liquid coating is filled into a container to obtain a filler; annular soft felt is stacked to obtain a soft felt precursor;
[0039] (b) A space for accommodating the filler is processed in the soft felt precursor, and the filler is filled into the soft felt precursor to obtain a cured felt preform;
[0040] (c) The cured felt blank is subjected to heating and rotation treatment and first cooling.
[0041] The method for preparing the solid felt is simple and does not require complex processes and equipment. A filler is placed in the soft felt precursor, and several annular cavities are formed inside the solid felt by heating, rotating and cooling. The solid felt prepared by this method has good thermal insulation performance, while also taking into account the advantages of stability, conductivity and durability.
[0042] Since the solidified felt is processed in layers, during the preform making process, the soft felt is cut into ring-shaped soft felts and stacked. When stacked to the annular cavity, a filler containing a liquid coating is used to fill it. Depending on the number and position of the annular cavities, the filler is placed when the soft felt is stacked to the position of the annular cavity. After a solidified felt preform is made, it is heated and cured in a high-temperature furnace. A rotating device needs to be installed in the high-temperature furnace to rotate the solidified felt preform. The rotating device includes, but is not limited to, rollers, or other devices that can make the solidified felt preform rotate and roll. When the temperature reaches the melting point of the liquid coating container, the liquid coating flows out, and the roller device is started to roll, so that the liquid coating can be evenly adsorbed on the surface of the annular cavity. At high temperature, the water in the coating will evaporate and solidify. After the high-temperature curing process is completed, the liquid coating cools and solidifies, thus forming an annular cavity inside the solidified felt preform, and then proceeding with the subsequent process.
[0043] To prevent the liquid coating from being squeezed during the preform preparation process, the liquid coating is filled into a container, and a space for accommodating the filler is machined into the soft felt precursor.
[0044] The size, shape, and position of the container used to fill the liquid coating are determined by the annular cavity. This container will melt when exposed to high temperatures, and the liquid coating can then be filled into the container.
[0045] Furthermore, the temperature of the heating and rotation treatment is ≥230℃, including but not limited to any one of 230℃, 250℃, 280℃, 300℃, 330℃, 350℃, 380℃ or 400℃, or a range between any two.
[0046] Furthermore, the heating and rotation treatment time is 2 to 4 hours (for example, it can be any one of 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours or any range between two), and the isothermal heat treatment time is 0.5 to 2 hours (for example, it can be any one of 0.5 hours, 1 hour, 1.5 hours or 2 hours or any range between two).
[0047] Furthermore, the rotation speed of the heating and rotating process is 0.05 to 0.2 rpm, including but not limited to any one of 0.05 rpm, 0.1 rpm, 0.15 rpm or 0.2 rpm, or any range between two of them.
[0048] By controlling the temperature, time, and rotation speed of the heating and rotating process, the liquid coating can be evenly distributed on the surface of the annular cavity, keeping the curing coating within a reasonable range. Heating causes the moisture in the liquid coating to vaporize, thus solidifying the coating. Rotation ensures that the liquid coating evenly covers the cavity surface, achieving the cavity effect.
[0049] Furthermore, the melting point of the container is 100 to 500°C, including but not limited to 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, or 500°C.
[0050] Furthermore, the annular soft felt is impregnated with resin, and the impregnation process can be a conventional impregnation process in the art.
[0051] Further, based on parts by weight, the liquid coating comprises the following components:
[0052] The ingredients include 5-6 parts binder, 4-5 parts graphite, 21-23 parts silicon carbide, 1-2 parts carbon fiber powder, 0.5-2 parts fumed silica powder, 9-11 parts triethanolamine borate, 7-9 parts additives, 33-37 parts water, and 10-15 parts anhydrous ethanol.
[0053] Furthermore, the first cooling process also includes: a first carbonization treatment, a heat treatment, machining, a hardening treatment, a second carbonization treatment, and a surface treatment.
[0054] Furthermore, the temperature of the first carbonization treatment is 700 to 1000°C, including but not limited to any one of 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, or a range between any two.
[0055] Furthermore, the first carbonization treatment time is 20 to 26 hours, including but not limited to the point value of any one of 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours or 26 hours or the range value between any two.
[0056] The first carbonization process involves decomposing materials into carbon-based compounds at high temperatures. This process primarily increases the carbon content of the material by evaporating or dissolving non-carbon elements at high temperatures, thereby increasing its electrical conductivity. Higher temperatures result in smaller interlayer spacing of the graphite in the carbonized sample, increasing the structural order of the sample. This process is crucial for improving the conductivity and stability of materials, especially in the photovoltaic field, where it can enhance the performance and lifespan of photovoltaic materials.
[0057] Furthermore, the temperature of the heat treatment is 1800 to 2000°C, including but not limited to any one of 1800°C, 1830°C, 1850°C, 1880°C, 1900°C, 1930°C, 1950°C, 1980°C or 2000°C, or a range between any two.
[0058] Furthermore, the heating treatment time is 20 to 26 hours, including but not limited to any one of 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, or 26 hours, or a range between any two.
[0059] In the photovoltaic field, materials undergo high-temperature heat treatment to achieve specific physical or chemical properties. This invention involves heat treatment at specific temperatures and times to obtain excellent thermal shock resistance, high strength, and high toughness. This treatment not only improves the durability and stability of materials but also effectively reduces production energy consumption and extends equipment lifespan, thereby lowering overall production costs.
[0060] Furthermore, the hardening process specifically includes: applying AB adhesive to the surface of the cured felt blank and then hardening it.
[0061] Furthermore, the temperature of the second carbonization treatment is 2195 to 2205°C, including but not limited to any one of 2195°C, 2196°C, 2197°C, 2198°C, 2199°C, 2200°C, 2201°C, 2202°C, 2203°C, 2204°C or 2205°C, or a range between any two.
[0062] Furthermore, the second carbonization treatment time is 25 to 30 hours, including but not limited to the point value of any one of 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours or the range value between any two.
[0063] The second carbonization process can improve the electrical conductivity and heat resistance of the solid felt, thereby enhancing its efficiency and lifespan in photovoltaic systems.
[0064] Furthermore, the surface treatment specifically includes:
[0065] After the surface treatment coating is applied to the surface of the cured felt blank that has undergone the second carbonization treatment, it is dried, cooled, and calcined.
[0066] Furthermore, the drying temperature is 145 to 155°C, including but not limited to any one of 145°C, 147°C, 149°C, 151°C, 153°C or 155°C, or a range between any two.
[0067] Furthermore, the drying time is 1 to 2 hours, including but not limited to any one of 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours or 2 hours, or any range between two of them.
[0068] Furthermore, the calcination temperature is 1750–1850°C, including but not limited to any one of 1750°C, 1760°C, 1770°C, 1780°C, 1790°C, 1800°C, 1810°C, 1820°C, 1830°C, 1840°C, or 1850°C, or a range between any two.
[0069] Furthermore, the calcination time is 0.8 to 1.2 hours, including but not limited to any one of 0.8 hours, 0.9 hours, 1.0 hours, 1.1 hours or 1.2 hours, or any range between two of them.
[0070] Furthermore, the coating thickness of the surface treatment coating is 1 to 3 mm, including but not limited to a point value of any one of 1 mm, 1.5 mm, 2 mm, 2.5 mm or 3 mm or a range between any two.
[0071] Further, based on parts by weight, the surface treatment coating comprises the following components:
[0072] The composition includes 5-6 parts binder, 4-5 parts graphite, 21-23 parts silicon carbide, 1-2 parts carbon fiber, 0.5-2 parts fumed silica, 9-11 parts triethanolamine borate, 7-9 parts additives, and 46-49 parts solvent.
[0073] In some specific embodiments, in the surface treatment coating, the binder, by weight parts, can be, for example, but not limited to, any one of 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, or 6 parts, or a range between any two; graphite can be, for example, but not limited to, any one of 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, or 5 parts, or a range between any two; silicon carbide can be, for example, but not limited to, any one of 21 parts, 21.2 parts, 21.4 parts, 21.6 parts, 21.8 parts, 22 parts, 22.2 parts, 22.4 parts, 22.6 parts, 22.8 parts, or 23 parts, or a range between any two; carbon fiber can be, for example, but not limited to, any one of 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, or 2 parts, or a range between any two; fumed silica can be, for example, The value may be, for example, but is not limited to, any one of 0.5 parts, 0.7 parts, 0.9 parts, 1.1 parts, 1.3 parts, 1.5 parts, 1.7 parts, or 2 parts, or a range between any two; triethanolamine borate may be, for example, but is not limited to, any one of 9 parts, 9.2 parts, 9.4 parts, 9.6 parts, 9.8 parts, 10.0 parts, 10.2 parts, 10.4 parts, 10.6 parts, 10.8 parts, or 11 parts, or a range between any two. The range of values; the additive can be, for example, but not limited to, any one of 7 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts, 8 parts, 8.2 parts, 8.4 parts, 8.6 parts, 8.8 parts or 9 parts, or any range of values between any two; the solvent can be, for example, but not limited to, any one of 46 parts, 46.5 parts, 47 parts, 47.5 parts, 48 parts, 48.5 parts or 49 parts, or any range of values between any two.
[0074] In surface treatment coatings and cured coatings, carbon fiber powder provides strength and rigidity, enhancing the mechanical properties of the coating; graphite powder provides lubricity and conductivity, helping to improve the physical properties of the felt coating; the binder firmly binds the other components together to form a stable coating structure; the curing agent acts as a catalyst during the curing process, accelerating the curing reaction of the binder and increasing the hardness of the felt coating.
[0075] Furthermore, the solvent comprises, by weight, 34-35 parts water and 12-14 parts ethanol. Ethanol, as a solvent, helps adjust the viscosity and flowability of the mixture, facilitating application and uniform distribution.
[0076] Furthermore, the annular soft felt includes, but is not limited to, at least one of: polyacrylonitrile-based carbon felt, polyacrylonitrile-based graphite felt, viscose-based carbon felt, viscose-based graphite felt, pre-oxidized fiber carbon felt, or pre-oxidized fiber graphite felt.
[0077] Another aspect of the present invention relates to a semiconductor crystal manufacturing apparatus, comprising the aforementioned solid felt or a solid felt prepared by the aforementioned solid felt preparation method.
[0078] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0079] Example 1
[0080] The solid felt provided in this embodiment includes: a substrate and a plurality of annular cavities disposed inside the substrate; the surface of the annular cavities is provided with a cured coating; the diameter of the annular cavity is 30 mm; the number of annular cavities per unit area is 550; and the distance between two adjacent annular cavities is 30 mm.
[0081] The method for preparing the solid felt provided in this embodiment includes the following steps:
[0082] 1. Take out the soft felt raw material, put the soft felt raw material into the equipment for impregnation with glue, so that the glue and soft felt raw material are fully mixed, take out the soft felt raw material and let it dry for later use.
[0083] 2. The liquid coating is filled into a container to obtain a filler; the melting point of the container is 100℃;
[0084] By weight, liquid coatings comprise the following components:
[0085] The composition includes 5.5 parts furan resin, 4.5 parts graphite, 22 parts silicon carbide, 1.5 parts carbon fiber powder, 1 part fumed silica powder, 10 parts triethanolamine borate, 8 parts additives, 35 parts water, and 13 parts anhydrous ethanol; the additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:2.
[0086] 3. Cut the soft felt raw material into ring-shaped soft felts, stack them, process the ring-shaped soft felts at the positions that form ring cavities to create spaces that can accommodate the filler, fill the spaces with the filler, and continue to stack the ring-shaped soft felts to obtain a solidified felt blank.
[0087] 4. The cured felt blank is subjected to heating and rotation treatment and first cooling; the heating and rotation treatment temperature is 230℃, the heating time is 3h, the constant temperature heat treatment time is 1h, and the rotation speed is 0.1 rpm.
[0088] 5. After the first cooling, the process includes a first carbonization treatment, a heat treatment, machining, hardening treatment, and a second carbonization treatment. The temperature of the first carbonization treatment is 700℃ and the time is 23 hours. The temperature of the heat treatment is 1800℃ and the time is 23 hours. The temperature of the second carbonization treatment is 2200℃ and the time is 27 hours.
[0089] 6. After coating the surface of the cured felt blank with a surface treatment coating of 95μm thickness, the blank is dried, cooled a second time, and calcined. The drying temperature is 145℃ and the time is 1h. The calcination temperature is 1750℃ and the time is 0.8h.
[0090] By weight, surface treatment coatings comprise the following components:
[0091] The composition includes 5.5 parts furan resin, 4.5 parts graphite, 22 parts silicon carbide, 1.5 parts carbon fiber, 1 part fumed silica, 10 parts triethanolamine borate, 8 parts additives, 34.5 parts water, and 13 parts ethanol. The additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:2.
[0092] Example 2
[0093] The solid felt provided in this embodiment includes: a substrate and a plurality of annular cavities disposed inside the substrate; the surface of the annular cavities is provided with a cured coating; the diameter of the annular cavity is 20 mm; the number of annular cavities per unit area is 350; and the distance between two adjacent annular cavities is 40 mm.
[0094] The method for preparing the solid felt provided in this embodiment includes the following steps:
[0095] 1. Same as Example 1;
[0096] 2. The liquid coating is filled into a container to obtain a filler; the melting point of the container is 100℃;
[0097] By weight, liquid coatings comprise the following components:
[0098] The composition includes 5 parts furan resin, 4 parts graphite, 21 parts silicon carbide, 1 part carbon fiber powder, 0.5 parts fumed silica powder, 9 parts triethanolamine borate, 7 parts additives, 33 parts water, and 10 parts anhydrous ethanol; the additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:1.
[0099] 3. Same as Example 1;
[0100] 4. The cured felt blank is subjected to heating and rotation treatment and first cooling; the heating and rotation treatment temperature is 250℃, the heating time is 4h, the constant temperature heat treatment time is 0.5h, and the rotation speed is 0.05 rpm.
[0101] 5. After the first cooling, the process includes a first carbonization treatment, a heat treatment, machining, hardening treatment, and a second carbonization treatment. The temperature of the first carbonization treatment is 800℃ and the time is 23 hours. The temperature of the heat treatment is 1850℃ and the time is 20 hours. The temperature of the second carbonization treatment is 2200℃ and the time is 27 hours.
[0102] 6. After coating the surface of the cured felt blank with a surface treatment coating of 100μm thickness, the material is dried, cooled a second time, and calcined. The drying temperature is 147℃ and the time is 1.5h. The calcination temperature is 1780℃ and the time is 0.9h.
[0103] By weight, surface treatment coatings comprise the following components:
[0104] The composition includes 5 parts furan resin, 4 parts graphite, 21 parts silicon carbide, 1 part carbon fiber, 0.5 parts fumed silica, 9 parts triethanolamine borate, 7 parts additives, 34 parts water, and 12 parts ethanol. The additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:1.
[0105] Example 3
[0106] The solid felt provided in this embodiment includes: a substrate and a plurality of annular cavities disposed inside the substrate; the surface of the annular cavities is provided with a cured coating; the diameter of the annular cavity is 25 mm; the number of annular cavities per unit area is 790; and the distance between two adjacent annular cavities is 50 mm.
[0107] The method for preparing the solid felt provided in this embodiment includes the following steps:
[0108] 1. Same as Example 1;
[0109] 2. The liquid coating is filled into a container to obtain a filler; the melting point of the container is 100℃;
[0110] By weight, liquid coatings comprise the following components:
[0111] The composition includes 6 parts furan resin, 5 parts graphite, 23 parts silicon carbide, 2 parts carbon fiber powder, 2 parts fumed silica powder, 11 parts triethanolamine borate, 9 parts additives, 37 parts water, and 15 parts anhydrous ethanol; the additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:3.
[0112] 3. Same as Example 1;
[0113] 4. The cured felt blank is subjected to heating and rotation treatment and first cooling; the heating and rotation treatment temperature is 280℃, the heating time is 2h, the constant temperature heat treatment time is 2h, and the rotation speed is 0.2 rpm.
[0114] 5. After the first cooling, the process includes a first carbonization treatment, a heat treatment, machining, hardening treatment, and a second carbonization treatment. The temperature of the first carbonization treatment is 900℃ and the time is 23 hours. The temperature of the heat treatment is 1950℃ and the time is 26 hours. The temperature of the second carbonization treatment is 2205℃ and the time is 25 hours.
[0115] 6. After coating the surface of the cured felt blank with a surface treatment coating of 105μm thickness, the material is dried, cooled a second time, and calcined. The drying temperature is 150℃ and the time is 1.8h. The calcination temperature is 1830℃ and the time is 1.1h.
[0116] By weight, surface treatment coatings comprise the following components:
[0117] The composition includes 6 parts furan resin, 5 parts graphite, 23 parts silicon carbide, 2 parts carbon fiber, 2 parts fumed silica, 11 parts triethanolamine borate, 9 parts additives, 35 parts water, and 14 parts ethanol. The additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:3.
[0118] Example 4
[0119] The solid felt provided in this embodiment includes: a substrate and a plurality of annular cavities disposed inside the substrate; the surface of the annular cavities is provided with a cured coating; the diameter of the annular cavity is 30 mm; the number of annular cavities per unit area is 610; and the distance between two adjacent annular cavities is 60 mm.
[0120] The method for preparing the solid felt provided in this embodiment includes the following steps:
[0121] 1. Same as Example 1;
[0122] 2. The liquid coating is filled into a container to obtain a filler; the melting point of the container is 100℃;
[0123] By weight, liquid coatings comprise the following components:
[0124] The composition includes 5 parts furan resin, 5 parts graphite, 23 parts silicon carbide, 2 parts carbon fiber powder, 0.5 parts fumed silica powder, 9 parts triethanolamine borate, 7 parts additives, 33 parts water, and 15 parts anhydrous ethanol; the additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:2.
[0125] 3. Same as Example 1;
[0126] 4. The cured felt blank is subjected to heating and rotation treatment and first cooling; the heating and rotation treatment temperature is 300℃, the heating time is 2.5h, the constant temperature heat treatment time is 1.5h, and the rotation speed is 0.1 rpm.
[0127] 5. After the first cooling, the process includes a first carbonization treatment, a heat treatment, machining, hardening treatment, and a second carbonization treatment. The temperature of the first carbonization treatment is 1000℃ and the time is 23 hours. The temperature of the heat treatment is 2000℃ and the time is 23 hours. The temperature of the second carbonization treatment is 2195℃ and the time is 30 hours.
[0128] 6. After coating the surface of the cured felt blank with a surface treatment coating of 98μm thickness, the blank is dried, cooled a second time, and calcined. The drying temperature is 155℃ and the time is 2h. The calcination temperature is 1850℃ and the time is 1.2h.
[0129] By weight, surface treatment coatings comprise the following components:
[0130] The composition includes 5.4 parts furan resin, 4.7 parts graphite, 21.3 parts silicon carbide, 1.9 parts carbon fiber, 0.8 parts fumed silica, 9.5 parts triethanolamine borate, 7.7 parts additives, 34.6 parts water, and 12.5 parts ethanol. The additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:2.
[0131] Comparative Example 1
[0132] The only difference between this comparative example and Example 1 is that no annular cavity was provided in the matrix.
[0133] Comparative Example 2
[0134] The only difference between this comparative example and Example 1 is that the number of annular cavities per unit area is 100.
[0135] Comparative Example 3
[0136] The only difference between this comparative example and Example 1 is that the number of annular cavities per unit area is 850.
[0137] Experimental Example
[0138] The heat insulation, stability and conductivity of the solid felt in each embodiment and comparative example were tested. The heat insulation was judged by the output heater power. When the power was reduced, the heat insulation was good. The results are shown in Table 1.
[0139] Table 1
[0140]
[0141]
[0142] As can be seen from Table 1, the more cavities there are, the higher the insulation performance. However, if there are too many cavities, the cavities will be too close together, which will lead to a decrease in the strength of the felt.
[0143] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a solid felt, characterized in that, The prepared solid felt includes: a matrix and several annular cavities disposed inside the matrix; The surface of the annular cavity is provided with a cured coating; The diameter of the annular cavity is 20~30mm; The number of annular cavities set within the unit area is 350 to 790, with the cross-sectional area of the solid felt per square meter as the unit area. The distance between two adjacent annular cavities is 30~60mm; The thickness of the cured coating is 2~4mm; The method includes the following steps: (a) The liquid coating is filled into a container to obtain a filler; the annular soft felt is stacked, and the annular soft felt is processed at the position where the annular cavity is formed to create a space that can accommodate the filler. The filler is filled into the processed space, and the annular soft felt is stacked to obtain a cured felt blank. (b) The cured felt blank is subjected to heating and rotation treatment and first cooling; during the heating and rotation treatment, when the temperature reaches the melting point of the container of liquid coating, the liquid coating flows out, heating causes the water in the liquid coating to vaporize, so that the liquid coating is cured to form a cured coating, and rotation causes the liquid coating to be evenly coated on the cavity surface to achieve the cavity effect.
2. The method for preparing the solid felt according to claim 1, characterized in that, The liquid coating comprises the following components by weight: The ingredients include 5-6 parts binder, 4-5 parts graphite, 21-23 parts silicon carbide, 1-2 parts carbon fiber powder, 0.5-2 parts fumed silica powder, 9-11 parts triethanolamine borate, 7-9 parts additives, 33-37 parts water, and 10-15 parts anhydrous ethanol.
3. The method for preparing the solid felt according to claim 2, characterized in that, The adhesive comprises: furan resin; And / or, the additives include yttrium silicate and aluminum tantalate in a mass ratio of 1:1 to 3.
4. The method for preparing the solid felt according to claim 1, characterized in that, Includes at least one of the following technical features: (1) The temperature of the heating and rotation treatment is ≥230℃; (2) The heating and rotation treatment time is 2-4 hours, and the constant temperature heat treatment time is 0.5-2 hours; (2) The rotation speed of the heating and rotating process is 0.05~0.2 rpm.
5. The method for preparing the solid felt according to claim 1, characterized in that, The annular soft felt is impregnated with resin.
6. The method for preparing the solid felt according to claim 1, characterized in that, The first cooling process also includes: a first carbonization treatment, a heat treatment, machining, a hardening treatment, a second carbonization treatment, and a surface treatment.
Citation Information
Patent Citations
Sewer deodorant aromatic pellet with controlled release function and manufacturing method thereof
CN104840988A
Carbon fiber hard felt surface coating and preparation process thereof
CN116289238A
Reinforced heat shield felt insulation structure
CN211897173U
Method and apparatus for forming corrosion-resistant coating on cylindrical container inner surface
JP2000268784A